(untitled) (Jurnal Manajemen Bisnis, 2026)
This study aims to analyze the effect of National Electricity Consumption on National Productivity, proxied by Indonesia’s Gross Domestic Product (GDP), and to examine the moderating roles of the Producer Price Index (PPI) and Micro and Small Enterprise (MSE) Output in this relationship. Theoretically, this study integrates Transmission Mechanism Theory, Cost-Push Theory, and Input-Output Analysis to explain that the relationship between electricity consumption and GDP is influenced by the absorption capacity of the real sector and production cost pressures. This study uses secondary data for the period 2010–2023 obtained from Statistics Indonesia (BPS), PT PLN (Persero), and the Ministry of Energy and Mineral Resources, employing a regression approach with a moderation model to test direct and interaction effects. The results indicate that National Electricity Consumption does not have a statistically significant effect on GDP, and neither PPI nor MSE Output significantly moderates this relationship. These findings suggest that the relationship between electricity consumption and economic growth cannot be empirically supported within the specified model and indicate limitations in model specification as well as potential multicollinearity issues. Conceptually, the results remain relevant to theoretical frameworks emphasizing the importance of structural conditions such as price stability and real sector capacity; however, policy implications should be interpreted cautiously. This study contributes by highlighting the need for careful interpretation of the energy–growth relationship and the importance of more appropriate methodological approaches in future research.